Clement of Alexandria’s Gnostic Exposition of the Decalogue - Edwards, Robert G. T (Journal of early Christian studies, 2015)
Clement of Alexandria’s only explicitly stated “gnostic exposition” of the Bible occurs in Stromateis 6.16, the subject of which is the Decalogue. This paper examines what is particularly “gnostic” about this “gnostic exposition” by examining Clement’s extensive use of the ἐγκύκλιος παιδεία, along with the more explicitly (truly) “gnostic” aspects of the interpretation. Through these examinations of the “gnostic exposition,” it is concluded that Clement’s interpretation is delivered to the true Gnostic, and that Clement is teaching through a veil—by way of “hints”—in order to show the Gnostic his/her role as the teacher of the Church.